UPAYA MENINGKATKAN HASIL BELAJAR KOGNITIF GEOGRAFI SISWA KELAS X MELALUI PENERAPAN SOAL EVALUASI BENTUK URAIAN DI SMAN 61 JAKARTA - Azizah, Sarah Ummu (Universitas Nusa Cendana, 2024)
This study aims to describe the efforts made through research on the application of evaluation questions in the form of descriptions in order to improve students' cognitive geography learning outcomes. Data collection was carried out for five weeks, from March to May 2023, with a total of 36 students for the experimental class group. The instrument used is a formative test of lithosphere material with 8 questions in the form of descriptions as an instrument applied to the trial application of evaluation questions in the form of descriptions to improve student learning outcomes. The method used in this research is descriptive quantitative, with experimental approach, and a pretest-posttest control group design. Based on the results of data calculation and processing, it was found that the description questions applied to the lithosphere material chapter were able to improve student learning outcomes by 7.28. And based on the data obtained from the research results, it shows that the application of evaluation questions in the form of descriptions is able to increase the percentage of completeness of student learning outcomes compared to the previous chapter, the basics of geography chapter, which uses multiple choice evaluation questions, namely from seventy percent to eighty-six percent, or by sixteen percent.